The relationship between self-confidence and concentration with the ability to smash volleyball athletes 12-17 years old in pervas club - Indah Zunita; Hardopo Putro, Kukuh; Nadine Nata Safitri; Edward Viktoryan Raymon Kalaibin; Muhammad Rizqi Eka Putra; Muhammad Izzudin Al Haq; Faros Shouma Askalani; Ananda Kirani Yulia; Lavaya Yuri Andjan; Umair Ansharullah Azzam (Jorpres (Jurnal Olahraga Prestasi), 2025)
This study aims to determine (1) The relationship between self-confidence and the ability to smash volleyball athletes 12-17 years at the Pervas club. (2) The relationship between concentration and the ability to smash volleyball athletes 12-17 years at the Pervas club. (3) The relationship between selfconfidence and concentration with the ability to smash volleyball athletes 12-17 years old at the Pervas club. This research is quantitative research with correlation. The study population was volleyball 12-17 years at the Pervas club, totaling 54 athletes. The sampling technique used purposive sampling. The criteria are (1) not in pain, (2) aged 12-17 years, (3) have participated in matches, (4) still actively practicing. Based on these criteria, there were 46 athletes who met. Self-confidence and concentration instruments use questionnaires, while smash ability uses smash ability tests. Data analysis using multiple regression. The results showed that: (1) There is a significant relationship between self-confidence and smash ability in volleyball athletes 12-17 years old at the Pervas club, with a t value of 2.639> t table 2.017, sig. 0.012 and an effective contribution of 14.14%. (2) There is a significant relationship between concentration and smash ability in volleyball athletes 12-17 years old at Pervas club, with t count 2.080 > t table 2.017, sig. 0.044 and an effective contribution of 9.36%. (3) There is a significant relationship between confidence and concentration with smash ability in volleyball athletes 12-17 years old at Pervas club, with F count 6.615 > F table (2; 43) 3.21 and sig. 0.003 and an effective contribution of 23.50%.